First searches for optical counterparts to gravitational-wave candidate events - The LIGO Scientific Collaboration; The Virgo Collaboration; Sokolowski, Marcin (Institute of Physics Publishing, Inc., 2014)
During the Laser Interferometer Gravitational-wave Observatory and Virgo joint science runs in 2009-2010, gravitational wave (GW) data from three interferometer detectors were analyzed within minutes to select GW candidate events and infer their apparent sky positions. Target coordinates were transmitted to several telescopes for follow-up observations aimed at the detection of an associated optical transient. Images were obtained for eight such GW candidates. We present the methods used to analyze the image data as well as the transient search results. No optical transient was identified with a convincing association with any of these candidates, and none of the GW triggers showed strong evidence for being astrophysical in nature. We compare the sensitivities of these observations to several model light curves from possible sources of interest, and discuss prospects for future joint GW-optical observations of this type.